PROYECTO DE FACTIBILIDAD PARA LA CREACIÓN DE UNA EMPRESA PRODUCTORA Y COMERCIALIZADORA DE SHAMPOO, A BASE DE CAFÉ, EN LA CIUDAD DE LOJA - Quezada Parra, Carlos Cornelio (2016)
The next study: "FEASIBILITY PROJECT FOR THE ESTABLISHMENT OF A PRODUCER AND DISTRIBUTOR OF SHAMPOO COMPANY BASE OF COFFEE IN THE CITY OF LOJA", is aimed at determining the appropriateness of whether to invest in a business like this, because draws our attention to the lack of these industries and all in general in our city, despite the existence of many existing natural resources and human talent. In search of the foregoing, the information needed to accept or reject this project from the point of commercial, legal, administrative financially and ending with a business valuation as proposed by quantifying the relationship is obtained Benefit-Cost , IRR, NPV and sensitivity analysis for different options. Thus we have; in its first phase the market study which contains all the results and tabulations of surveys for both consumers and owners of premises where the products that constitute our direct or indirect competition is sold. It is built with previous data a marketing plan where referring to product, price, place infrastructure or place of aspects such as marketing and communication strategy and advertising. Then we formulate the technical aspects where the size of the company and the capacity used is shown predicts work 60 %% for the first year because it is a new brand and not known yet, for the second year is expected to work 70% of capacity, for the third 80 % for the fourth and plans to realize 90% of installed capacity and 100% in the fifth year. 5 Within this study emphasis is also made to the macro location, micro location and description of the tools and equipment. Since the financial study indicates budgets, the State of Income, Balance Point, Cash Flow, the NPV of the project (539,080.06), the benefit-cost ratio that allows us to measure the performance obtained is calculated for each monetary amount invested and thus decide whether or not to accept project based on: If the ratio is greater than 1 the project is profitable, the result obtained by the project is greater than 1 (1.49), the which is favorable; we also have the IRR (45.32%), capital recovery period (which allows to know the time that has to recover the initial investment. In the case of project time to recover capital investment is 3 years, 10 months and 2 days,and at the end of this study is the sensitivity analysis (not only the degree of elasticity of the profitability of the project) Finally, disclosed the findings and recommendations of the Project Investment.